Hydrogels in applications for tissue engineering - Chng, Siaw Wei (2014)
Tissue engineering has brought across a lot of advancement to achieve life-saving and life-improving solutions for patients where some suitable medical treatment do not meet the desired outcome. One of the promising technologies which offer numerous attractive features is cell encapsulation. Cell encapsulation technology has advantages of offering tissue-like environment for cell/tissue growths and enhances cell differentiation and proliferation, and biodegradable. In this review, various application of cell encapsulation in tissue engineering and medical field such as cancer therapeutic, central nervous system diseases, cardiovascular and liver diseases will be discussed.